5-Year Survival in Gastric Adenocarcinoma with Epithelial and Stromal Versican Expression - Mohammad Hossein Sanei; Omid Mirmosayyeb; Ali Chehrei; Jamshid Ansari; Elahe Saberi (Iranian Society of Pathology, 2019)
Background & Objective: Gastric cancer is the second most frequent cause of cancer death worldwide, despite differences in incidence around the world. The majority of gastric cancer cases concern gastric adenocarcinoma, which has a fairly high 5-year survival rate when coupled with early-stage diagnosis. Versican, a member of the aggregating chondroitin sulfate proteoglycans family, is accumulated predominantly in the tumor stroma. The aim of our study was to investigate versican expression in gastric adenocarcinoma. Methods: In this study we investigated 80 patients with gastric adenocarcinoma who underwent gastrectomy. Each sample was obtained from paraffin-embedded resected specimens of the stomach after histopathological diagnosis. Patient follow-up was performed every 3 months after the beginning of data collection. Survival analysis was calculated using the Kaplan-Meier method for univariate analysis.Results: Out of 80 patients with gastric adenocarcinoma, 76 cases (76.3%males and 23.7% females) completed the follow-up period. Positive versican expression in tumor epithelial and stromal cells was found in 39.5% and 22.4% of tumors, respectively. Shorter survival was observed among patients whose gastric adenocarcinoma expressed epithelial or stromal versican.Conclusion: In summary, the present study suggests that versican is likely a prognostic biomarker that predicts a poor outcome in patients with gastric adenocarcinoma. Comprehensive studies with larger sample sizes are needed.